Food security and nutrition - Gordon, I.J.; Alonso, Silvia; Crump, L.; Domínguez-Salas, Paula; Garine-Wichatitsky, M. de. (CAB International, 2021)
This chapter gives an overview of the relationship between food security and One Health. Topics that were highlighted are: the global governance of food and nutrition security; malnutrition; undernutrition; over nutrition; food waste; and systems approach to food security.